A study of the Malaysian non-Chinese undergraduate’s response in the mandarin speaking test - Yong, Ying Mei; Cheng, Ching Yee (2017)
Mandarin learners were trained to fluently communicate in spoken Mandarin is the communication purpose of language learning. The communication of spoken language mainly conducted in dialogue form. In daily conversation, one will usually deliver messages, express attitudes, social interact or request. The question-answer mechanism of spoken language includes the ability of listening and speaking. Firstly, one needs to understand a question before he or she responses through spoken language. The speaking test aims to examine the capability of learners’ spoken Mandarin that whether they can understand Mandarin questions and answer in spoken Mandarin through daily life topics in order to fulfill basic communication needs. Therefore, this paper intends to assess the Malaysian Non-Chinese Undergraduate’s responses in the Mandarin Speaking Test. The Mandarin Speaking Test in Universiti Malaysia Pahang (UMP) were designed based on the format of the Chinese Proficiency Test- Speaking Test (Hanyu Shuiping Kaoshi Koushi, HSKK), Beginners Level whereas the “Listen and Answer” part covered the content of Chinese Language Proficiency Scales for Speakers of Other Languages, Level 1 and 2. The paper structures the UMP’s Mandarin Speaking Test as research fundamental to measure the level of spoken Mandarin response among the Malaysia Non-Chinese undergraduate in Mandarin for Intermediate classes in UMP. Through the response type analysis, the paper discovers the Malaysian Non-Chinese undergraduate’s responses ability and their mastery of specific interrogative. The findings shown that the mastery level of spoken Mandarin responses is different among the Non-Chinese undergraduates. The paper aspires to contribute inspiration to Mandarin teachers in conducting Mandarin Speaking classes that consequently develop the teaching Mandarin industry.